2017
DOI: 10.1242/dev.149641
|View full text |Cite
|
Sign up to set email alerts
|

The matrix protein Tiggrin regulates plasmatocyte maturation inDrosophilalarva

Abstract: The lymph gland (LG) is a major source of hematopoiesis during Drosophila development. In this tissue, prohemocytes differentiate into multiple lineages, including macrophage-like plasmatocytes, which comprise the vast majority of mature hemocytes. Previous studies have uncovered genetic pathways that regulate prohemocyte maintenance and some cell fate choices between hemocyte lineages. However, less is known about how the plasmatocyte pool of the LG is established and matures. Here, we report that Tiggrin, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 83 publications
(108 reference statements)
0
11
0
Order By: Relevance
“…Dg binds ECM proteins like Perlecan, whose mutation causes reduced lymph gland growth and premature differentiation of the progenitors in the primary lobes . Similarly, the ECM protein Tiggrin was found to control the progression of intermediate progenitors to mature plasmatocytes (Zhang and Cadigan, 2017). Grigorian et al (2011) also suggested that hemocytes digest only a small part of the ECM to facilitate their dispersal and most of the ECM is left intact during metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dg binds ECM proteins like Perlecan, whose mutation causes reduced lymph gland growth and premature differentiation of the progenitors in the primary lobes . Similarly, the ECM protein Tiggrin was found to control the progression of intermediate progenitors to mature plasmatocytes (Zhang and Cadigan, 2017). Grigorian et al (2011) also suggested that hemocytes digest only a small part of the ECM to facilitate their dispersal and most of the ECM is left intact during metamorphosis.…”
Section: Discussionmentioning
confidence: 99%
“…The general view is that these lobes essentially harbor progenitors as initially suggested by the higher expression of DE-cadherin and the lack of expression of mature blood cell markers (Jung et al, 2005). Yet only few studies on progenitor differentiation in the primary lobe report on phenotypes in the secondary lobes (Owusu-Ansah and , Dragojlovic-Munther and Martinez-Agosto, 2013, Khadilkar et al, 2017b, Hao and Jin, 2017, Zhang and Cadigan, 2017, Kulkarni et al, 2011, Benmimoun et al, 2015. These studies revealed that posterior lobes could also differentiate in genetic contexts where there is extensive premature differentiation in primary lobes, however a thorough analysis of the posterior LG lobes is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Lymph glands that lack Tig are overall smaller than wild-type and without Tig, plasmatocyte differentiation occurs early within the primary and posterior lobes (Zhang et al 2014). Overexpression of Tig in Hml + cells does not alter crystal cell and lamellocyte formation, but it does inhibit P1 and Eater expression, and thus plasmatocyte maturation (Zhang and Cadigan 2017).…”
Section: Larval Lymph Gland: Zones Cells and Signalsmentioning
confidence: 99%
“…In addition to these phenotypes, extranumerary posterior lobes are seen in asrij mutant animals and ectopic PSC cells are present in the secondary lobes of jumu mutants (Kulkarni et al 2011; Khadilkar et al 2017). Premature differentiation is the most prominent defect observed in the posterior lobes in animals mutant for Tiggrin or upon wasp parasitization (Sorrentino et al 2002; Zhang and Cadigan 2017). These phenotypes indicate that the molecular mechanisms that regulate hemocyte differentiation within the primary and posterior lobes might be similar, although they are employed at distinct stages of development.…”
Section: Larval Lymph Gland: Zones Cells and Signalsmentioning
confidence: 99%
“…The ECM protein Tiggrin (Tig) has been identified as a downstream effector of Wg signaling [ 60 , 61 ]. In lymph glands, Wg signal inhibits the expression of Tig .…”
Section: Regulatory Signaling During Lymph Gland Developmentmentioning
confidence: 99%